Russian wheat aphid, Diuraphis noxia (Kurdjomov), ecology and reproduction on five noncultivated grass hosts in high elevation environments - Pucherelli, Sherri F., author; Peairs, Frank B., advisor; Cranshaw, Whitney, committee member; Hansen, Neil, committee member (Colorado State University. Libraries, 2010)
Russian wheat aphid ecology, occurrence, movement, and reproduction on five noncultivated grass hosts was examined in high elevation environments. The objectives of the first study were to: 1) identify Russian wheat aphid occurrence and abundance on five common grass hosts at elevations between 1,829- 2,743 m during June-October; 2) monitor Russian wheat aphid movement and flight patterns between 1,524- 2,743 m, with the use of suction traps; 3) describe the predator and competitor assemblages encountered by the Russian wheat aphid in high elevation environments; and 4) confirm Russian wheat aphid holocycly in North America by collecting sexual forms and eggs. Weekly aphid and predator collections were made from crested wheatgrass, intermediate wheatgrass, slender wheatgrass, western wheatgrass, and foxtail barley at 23 sites, between 1,829-2,743 min the Cache La Poudre River canyon, Larimer County, Colorado. Four suction traps were installed at 1,655, 1,992, 2,206, and 2,372 m to collect alate aphids. Russian wheat aphids were collected from all five grass hosts sampled. Russian wheat aphids were most prevalent in July and most commonly collected from crested wheatgrass. Other cereal aphid species were collected, including Diuraphis frequens, Sipha elegans, Rhopalosiphum padi, Sitobion avenae, and Schizaphis graminum. Sipha elegans was the most abundant aphid collected. The most Russian wheat aphids were collected in June in the trap at 1,655 m, coinciding with peak captures in nearby wheat production. Trap captures declined with increasing elevation. Russian wheat aphid populations in the Cache La Poudre canyon are likely maintained by both immigrant aphids and from local metapopulations within the canyon. Environmental conditions in high elevation environments could prompt the production of novel biotypes. The second study determined Russian wheat aphid biotype R W A2 reproductive and development rates on the same five noncultivated grass hosts to gain information about host quality, potential refuges and sources of selection pressure. Russian wheat aphid reproductive and development rates were measured at 18-24°C, on the five grass hosts sampled in the first study, and at 24-29°C, and 13-18°C on intermediate and crested wheatgrass. The intrinsic rates of increase for all five hosts were lower than those reported for susceptible and resistant wheats. Aphids feeding on crested and intermediate wheatgrass at the 13-18°C temperature had lower fecundity, fewer nymph production days, longer generational times, and lower intrinsic rate of increase than aphids feeding at the 18-24 °C temperature regime. Poor hosts pose greater selection pressures. The five noncultivated hosts tested were poor hosts in comparison to wheat, and their greater selection pressure might promote Russian wheat aphid genetic variability.
Keywords: Russian wheat aphid